Approximation of Periodic Functions of Bounded Variation by Some Positive Linear Operators. (4th July 2021) - Bustamante, Jorge
Abstract: We study the pointwise degree of approximation of periodic functions of bounded variation by positive linear polynomial operators. For the proof we used sub-additive majorants.